A MODEL FOR PRODUCT-INTEGRATION TECHNOLOGY FOR HIGHLY COMPLEX ENVIRONMENTS: AN EMPIRICAL STUDY OF Ti- 6Al-4V ALLOY TREATED WITH PULSED LASER Nd:YAG IN AEROSPACE INDUSTRY - Martins Oliveira, Selma Regina; Alves, Jorge Lino (European Scientific Journal, ESJ, 2014)
This article aims to contribute to a new planning policy in the innovative products development. To do so, it presents a new modeling proposal to integrate technological innovation and new product development (NPD) in Ti-6Al-4V Alloy Treated With Pulsed Laser Nd:YAG for turbines for Aerospace Industry, carried out according to the following stages: Phase 1: Modeling of the information needs; Phase 2: Determining of technology integration dimensions to the product; Phase 3: Evaluation of performance of technology integration dimensions to the product. To demonstrate the feasibility and plausibility of the modeling, a case study was conducted in a high tech company in Brazil (hypothetical application). The investigation was helped by the intervention of specialists with technical and scientific knowledge about the research object. To reduce subjectivity in the results, the following methods were used: Law of Categorical Judgment - psychometric scaling of Thurstone (1927), Multivariate Analysis statistical methods and method Compromise Programming, Electre III and Promethee II - multi-criteria analysis; and Neurofuzzy Technology. It is hoped that this study will stimulate a broad debate on the issue and it is acknowledged that more studies are needed to build more robust results in the near future. The results were satisfactory, validating the present proposal